Ethnic Mixing and Tolerance in Mathare Informal Settelment in Nairobi City, Kenya - Kyuvi, Stellamaries; Nzioka, Charles; Ayiemba, Elias (European Scientific Journal, ESJ, 2023)
In any multi-ethnic society, tolerance is regarded as an integral element for achieving social, economic, and political stability within the nation. Today, majority of the multi-ethnic nations in Africa struggle to promote ethno-cultural tolerance and acceptance among the diverse populations. Numerous African nations are embroiled in inter-state conflicts and civil wars stemming from ethnic differences, thereby presenting a dilemma regarding the promotion of ethnic pluralism. This paper focuses on examining whether ethnic mixing in the city can be a potential tool for promoting ethnic tolerance and peaceful co-existence. This can be further diffused to the rural regions and subsequently to the whole nation. The study adopted interpretive study design that utilized qualitative and quantitative methods in the collection and analysis of data. The initial survey involved interviews with 80 participants, while the in-depth interviews included 24 individuals. Participants were rural urban migrants who had lived in the city for more than five years and were at the time of study living in the Mathare informal settlement. Following the contact theory, the study found compelling evidence that exposure to different ethnic group promotes cultural learning and accommodation toward outgroups, resulting to individuals who are more open to diversity. The study proposes ethnic mixing and the creation of ethnic diverse spaces as an alternative strategy for promoting ethnic understanding and nationhood.